GENOME-WIDE ANALYSIS REVEALS THE MOLECULAR BASIS OF GENETIC VARIATION OF IMPORTANT ECONOMIC TRAITS IN CASHMERE GOATS ON QINGHAI-TIBET PLATEAU - dehong tian; kai zhao; Baicheng Zhou; Buying Han; Xue Li; Fei Tian; Delin Qi (Journal of Animal and Plant Sciences, 2023)
Qaidam Cashmere goat is one of the few animals that can survive in the harsh environment of the Qinghai-Tibet Plateau and the adjacent alpine areas. It has a strong adaptability, thus shaping the genetic diversity of goat phenotype, morphology, physiology and other aspects. However, the molecular basis behind these genetic mechanisms remains unclear. Here, we conducted genome-wide studies of genetic variation in two different morphologies and geographical coordinates in indigenous Chinese goats to identify selective signaling in genomic regions. In the present study, we resequenced 10 high-altitude Chinese indigenous goat breeds and compared them with low-altitude goats.By combining θπ and Fst values, we identified 1277 overlapping selection regions that may contribute to the wool fiber traits, reproductive performance, and high-altitude adaptation of goats.Candidate genes enriched in selected regions are associated with the phenotypes in cashmere fiber traits (IGFBP3, TNF, ROCK1, WNT10B, KITLG), reproduction traits (CAMK2D, IL-18, ESR1, ANAPC13), body size (POMC), hypoxic adaptation (TH, ACER1, GNB1, HIF1A) and disease (IL-10). This study provided valuable genetic information for the basis of biological characteristics and genetic improvement of breeds.
Keywords: cashmere goat; whole-genome resequencing; adaptability; candidate genes